A comparative study of nanoscale glass filler reinforced epoxy composites: Electrospun nanofiber vs nanoparticle. (6th June 2016) - Wang, Guolong; Yu, Demei; Mohan, Ram V.; Gbewonyo, Spero; Zhang, Lifeng
Abstract: Electrospun glass nanofibers (EGNFs) are emerging fillers to improve mechanical properties of polymer matrix composite materials. However, questions concerning their reinforcing effectiveness in comparison with other nanoscale fillers such as glass/silica nanoparticles (GNPs) are still to be answered because reinforcing mechanisms for conventional fiber reinforced polymer composites might not be applicable at distinctive nanometer scale. Herein a comparative study on reinforcing effect of EGNFs and their conventional counterpart GNPs was carried out for the first time. Four types of glass nanofillers, including pristine EGNFs and GNPs as well as amino surface-functionalized EGNFs and GNPs were investigated to make epoxy matrix nanocomposites at ultra-low loading level (≤0.5 wt%). Mechanical properties of these glass nanofiller reinforced epoxy composites were investigated and corresponding reinforcing and toughening mechanisms at nanometer scale were discussed. Due to shape factor (aspect ratio), EGNFs demonstrated much more pronounced reinforcing and toughening effectiveness and completely outperformed GNPs in all cases despite much lower specific surface area. This research provided meaningful data to fully understand the merit of EGNFs as reinforcing filler in polymer nanocomposites and paved the road for designing and modeling next-generation polymer matrix composite materials.